2014
DOI: 10.1002/anie.201311275
|View full text |Cite
|
Sign up to set email alerts
|

Probing Transient Conformational States of Proteins by Solid‐State R Relaxation‐Dispersion NMR Spectroscopy

Abstract: The function of proteins depends on their ability to sample a variety of states differing in structure and free energy. Deciphering how the various thermally accessible conformations are connected, and understanding their structures and relative energies is crucial in rationalizing protein function. Many biomolecular reactions take place within microseconds to milliseconds, and this timescale is therefore of central functional importance. Here we show that R1ρ relaxation dispersion experiments in magic-angle-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
169
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(173 citation statements)
references
References 25 publications
4
169
0
Order By: Relevance
“…Prior to the study of Lewandowski et al mentioned above, there have also been reports of measurements of 15 N R 1ϱ relaxation-rate constants in highly-deuterated proteins at lower MAS frequency of about 10-20 kHz [113], and over the last years several other studies of R 1ϱ rate constants have been reported under different conditions of sample deuteration, MAS frequency, and RF-field strengths [45,100,110,133,134]. The conditions under which coherent dephasing is sufficiently suppressed depends on the choice of the labeling scheme (in particular deuteration), the MAS frequency, and the RF field strength.…”
Section: Relaxation In Thementioning
confidence: 97%
See 3 more Smart Citations
“…Prior to the study of Lewandowski et al mentioned above, there have also been reports of measurements of 15 N R 1ϱ relaxation-rate constants in highly-deuterated proteins at lower MAS frequency of about 10-20 kHz [113], and over the last years several other studies of R 1ϱ rate constants have been reported under different conditions of sample deuteration, MAS frequency, and RF-field strengths [45,100,110,133,134]. The conditions under which coherent dephasing is sufficiently suppressed depends on the choice of the labeling scheme (in particular deuteration), the MAS frequency, and the RF field strength.…”
Section: Relaxation In Thementioning
confidence: 97%
“…In the case where the two exchanging states differ also in the orientations of dipolarcoupling and CSA tensors, the situation becomes more complex: as the RF-field amplitude approaches the rotary-resonance conditions [139,140] (ν 1 = n ν r where n = 1,2), we observe an increased R 1ϱ decay-rate constant [45,133,134]. This is expected, as the spectral density at the difference between MAS frequency and the RF-field amplitude is relevant for R 1ϱ (see Eq.…”
Section: Relaxation In Thementioning
confidence: 98%
See 2 more Smart Citations
“…This opens the way to rapid sequential assignment of backbone resonances (24)(25)(26)(27), as well as to the unambiguous measurement of detailed structural and dynamical parameters (28)(29)(30)(31)(32). A further increase in the MAS frequency to 100 kHz allows resonance assignment (20), a structure determination of a model protein (16), and interaction studies (15) with as little as 0.5 mg of sample.…”
mentioning
confidence: 99%